Sikkim State Draft Annual Plan 1985-86 - Planning Commission (Planning Commission, 1995)
The annual plan for 1985-86 represents the first year of the seventh plan. the total outlay proposed for the plan is Rs, 50.11 crores, the details of which are provided in the GN statement of the Seventh Five Year Plan document. Although the sectoral details and available in the main plan document a short summary of the proposals envisaged for 1985-86 sectorwise is given to facilitate consideration.
Planning and Development Department, Government of Sikkim